The Impact of YouTube and Facebook on the Achievement of Jordan University Students in English Language Course - Mohammad Faraj Saleh Al-Abdallat (University of Science and Technology, Yemen, 2018)
This study aimed to investigate the impact of YouTube and Facebook on the Achievement of Jordan University students in the English Language course, and the impact of the variables of GPA and the experience in e-learning. The study was conducted in the first semester of the academic year 2016/2017. The participants of the study were classified into three groups: two groups were experimental; the first group, of 16 participants, was taught using YouTube, and the second group, of 27 participants, was taught using Facebook whereas and the third one, of 34 participants, was set as a control group. Quasi-experimental method was used, and the two tools of the study were: an educational material designed in a manner consistent with the ways of the YouTube and Facebook, and an achievement test consisting of (25) items to measure the results of Jordan University students in the English Language. The validity and reliability of the study tools were checked and verified using standard. The results showed that there was a statistically significant effect in the results of the English language course at the Jordan University students due to the teaching method in favor of the two experimental groups, which were taught using the methods of the YouTube and Facebook. There were also statistically significant differences (α = 0.05) attributed to the GPA, and in favor of those with the Pass grade. Finally, there were statistically significant differences (α= 0.05) attributed to variables of limited experience, moderate experience and extensive experience, and in favor of those extensive experience. Keywords: Achievement, English language, Facebook, YouTube.